2023
DOI: 10.1002/jsfa.12474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taurine on rumen fermentation, nutrient digestion, rumen bacterial community and metabolomics and nitrogen metabolism in beef steers

Abstract: BACKGROUND The objectives of this study were to investigate the effects of taurine on rumen fermentation, rumen bacterial community and metabolomics, nitrogen metabolism and plasma biochemical parameters in beef steers. Six castrated Simmental steers (liveweight 402 ± 34 kg) and three levels of taurine (0, 20, 40 g d−1) were assigned in a replicated 3 × 3 Latin square design. Each experimental period included 15 days for adaptation and 5 days for sampling. RESULTS Supplementing taurine did not affect the rumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…g__Flexilinea was reported as a filamentous strictly anaerobic Gram-negative bacterium which could digest all kinds of carbohydrates (Wang et al, 2021). In addition, one study has reported that the abundance of g__norank_f__norank_o__RF39 was increased with the increase of NDF digestibility (Liu et al, 2023). We speculate that supplementation with 0.3% MI significantly improved the apparent digestibility of feed fiber, which was associated with the change in the abundance of g__Flexilinea and g__norank_f__norank_o__RF39.…”
Section: Discussionmentioning
confidence: 74%
“…g__Flexilinea was reported as a filamentous strictly anaerobic Gram-negative bacterium which could digest all kinds of carbohydrates (Wang et al, 2021). In addition, one study has reported that the abundance of g__norank_f__norank_o__RF39 was increased with the increase of NDF digestibility (Liu et al, 2023). We speculate that supplementation with 0.3% MI significantly improved the apparent digestibility of feed fiber, which was associated with the change in the abundance of g__Flexilinea and g__norank_f__norank_o__RF39.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, although microbes can affect the concentration of taurine in colon, the main factor affecting taurine metabolism in both the colon and plasma is L-cysteine, which is enhanced by NK4A214_group. Furthermore, taurine was found to increase the abundance of microbes in the colon, such as NK4A214_group and Ruminococcus [35]. Therefore, taurine conversely maintains microbial homeostasis.…”
Section: Discussionmentioning
confidence: 92%
“…In the same way, red ginseng polysaccharides have a positive effect on the production of short-chain fatty acids in the cattle rumen ( Ju et al, 2024 ). Oscillospiraceae_UCG-005 is also a class of cellulose-degrading bacteria in the rumen ( Li et al, 2021 ), but is also thought to play a role in the catabolism and utilization of dietary lipids, with significant increases in abundance, especially in animals exposed to high-fat diets ( Liu Y. et al, 2023 ; Wu Z. L. et al, 2023 ). This is consistent with the results of a decrease in apparent digestibility of ether extracts in the three groups of deer, although the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%